Analisa kualitas pelayanan menggunakan metode Service Quality (Servqual) dalam meningkatkan kepuasan nasabah (Study kasus: Bank Mandiri) - Rahadian, Muhammad Rajiv; Pangastuti, Nova; Parningotan, Sepriandi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Bank Mandiri is a company engaged in banking, insurance, and e-commerce. This study employs factor analysis to process the data, where this technique is used to group measurement indicators in the service quality measurement tool (Servqual) based on the proximity of each tested indicator. This study uses SERVQUAL, which consists of five dimensions to measure customer satisfaction with service companies, namely: Reliability, Responsiveness, Assurance, Empathy, and Tangibles. The calculation of thegapvalue per dimension shows that the Responsiveness dimension has the highestgapvalue of 0.56, indicating that this dimension has met respondents’ expectations. The overallgapcalculation shows that the overallgapvalue is 1.74, which means that the quality of service provided by PT Bank Mandiri Cabang Bekasi Juanda fully meets the needs and desires of the respondents. Based on the results of the research conducted to measure the service quality at PT Bank Mandiri Cabang Bekasi Juanda, it can be concluded that the calculation results using the Service Quality method show that the average actual value of customers is 71.32 and the average expected value of customers is 69.58, resulting in a positivegapvalue of 1.74, which indicates that customers are satisfied with the services provided by PT Bank Mandiri Cabang Bekasi Juanda